Oxaliplatin-based chemotherapy is more beneficial in KRAS mutant than in KRAS wild-type metastatic colorectal cancer patients. - Yu-Lin Lin; Yi-Hsin Liang; Jia-Huei Tsai; Jau-Yu Liau; Jin-Tung Liang; Been-Ren Lin; Ji-Shiang Hung; Liang-In Lin; Li-Hui Tseng; Yih-Leong Chang; Kun-Huei Yeh; Ann-Lii Cheng (PLoS ONE, 2014)
To identify better regimens in currently available chemotherapy would be beneficial to KRAS mutant metastatic colorectal cancer (mCRC) patients because they have fewer treatment options than KRAS wild-type mCRC patients. Clinicopathologic features and overall survival (OS) of KRAS mutant and wild-type mCRC patients who had used oxaliplatin-based, irinotecan-based, bevacizumab-based, as well as cetuximab-based regimens were compared to those who had never-used oxaliplatin-based, irinotecan-based, bevacizumab-based, as well as cetuximab-based regimens respectively. Between 2007 and 2012, a total of 394 mCRC patients, in whom 169 KRAS mutant and 225 KRAS wild-type, were enrolled. In KRAS mutant patients who had used oxaliplatin-based regimens (N = 131), the OS was significantly longer than that in KRAS mutant patients who had never-used oxaliplatin-based regimens (N = 38). The OS was 28.8 months [95% confidence interval (CI): 23.2-34.4] in KRAS mutant patients who had used oxaliplatin-based regimens versus 17.8 months [95% CI: 6.5-29.1] in KRAS mutant patients who had never-used oxaliplatin-based regimens (P = 0.026). Notably, OS in KRAS wild-type mCRC patients who had used oxaliplatin-based regimens (N = 185) was not significantly longer than that in KRAS wild-type mCRC patients who had never-used oxaliplatin-based regimens (N = 40) (P = 0.25). Furthermore, the OS in KRAS mutant patients who had used either irinotecan-based, bevacizumab-based or cetuximab-based regimens was not significantly different than that in KRAS mutant patients who had never-used either irinotecan-based, bevacizumab-based or cetuximab-based regimens respectively. In multivariate analyses, patients who had used oxaliplatin-based regimens remains an independent prognostic factor for longer OS in KRAS mutant mCRC patients. In conclusion, oxaliplatin-based regimens are more beneficial in KRAS mutant than in KRAS wild-type mCRC patients.